Prader Willi syndrome: endocrine updates and new medical therapies. Issue 1 (February 2020) - Harris, Rebecca M.; Stafford, Diane E.J.
Abstract : Purpose of review: Prader Willi syndrome is characterized not only by hyperphagia frequently resulting in obesity, but also by endocrine dysfunction across a variety of axes. This article reviews the most recent literature regarding possible causes of hyperphagia and the nature of endocrinopathies seen in Prader Willi syndrome, as well as current research into possible therapies. Recent findings: Investigation into neurologic, metabolic and hormonal drivers of hyperphagia and obesity has revealed new insights and clarified underlying pathophysiology. Additional studies continue to elucidate the hormonal deficiencies seen in the syndrome, allowing for improvements in clinical care. Summary: The underlying causes of the hyperphagia and progressive obesity frequently seen in Prader Willi Syndrome are largely unknown and likely multifactorial. Understanding the hormonal and metabolic drivers at work in PWS, as well as the nature of other hormonal dysfunction seen in the syndrome is necessary to guide current management and future research directions.